The form and content of modern english music and its application as a teaching tool in the classroom - Avila Villafuerte, Galo Eduardo (2012)
The theme of this thesis is The Form and Content of Modern English Music and Its Application as a Teaching Tool in the Classroom. This research was basically done in CENDIA, a private English institute located in the North of Quito, the capital of Ecuador. The sample was made up by forty female and male teenagers ranging from fourteen to twenty years old who belong to high and low middle class families.